2004
DOI: 10.1682/jrrd.2003.08.0131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of laser and ultrasound treatments on experimental wound healing in rats

Abstract: -A randomized controlled study investigated the effects of ultrasound and laser treatments on wound healing in rats. The duration of the inflammatory phase decreased with both laser and ultrasound treatments; however, laser was more effec-tive than ultrasound, with more significant results. The prolifera-tion phase showed, for both treatments, an increase in the level of hydroxyproline and the number of fibroblasts, as well as stimula-tion of the collagen synthesis and the composition. Laser treat-ment was aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 32 publications
2
30
0
9
Order By: Relevance
“…[11][12][13][14][15][16][17][18] Furthermore, studies in vivo and in vitro have demonstrated that laser increases ATP levels 15 and activates specific enzymes that accelerate tissue healing and repair, neovalcularization, [11][12][13][14][15]18 and increases in leukocyte phagocytic activity. 12,15 In addition, the laser effects are related to attenuation of painful symptoms in the diverse postoperative processes and mucosal lesions. 11,18 Cruz et al 9 demonstrated clinically that LLLT accelerates the orthodontic movement in humans.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Furthermore, studies in vivo and in vitro have demonstrated that laser increases ATP levels 15 and activates specific enzymes that accelerate tissue healing and repair, neovalcularization, [11][12][13][14][15]18 and increases in leukocyte phagocytic activity. 12,15 In addition, the laser effects are related to attenuation of painful symptoms in the diverse postoperative processes and mucosal lesions. 11,18 Cruz et al 9 demonstrated clinically that LLLT accelerates the orthodontic movement in humans.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Several methods have been used to study healing promotion, but few studies investigated these modalities in comparison to each other. [14][15][16][17][18] In this study we evaluated the effect of low-level laser in wound healing and compared it with phenytoin.…”
mentioning
confidence: 99%
“…13 Simi larly, in many ot her pub lis hed pa pers this be nefi ci al ef fect was ob ser ved bet we en the 5 th and 10th days. 22,27 Our fin ding is in ag re e ment with Bisht et al and ot hers. In this pe ri od, an gi o ge ne sis was found to be slightly hig her in la ser gro up.…”
Section: Discussionmentioning
confidence: 57%
“…In a li te ra tu re search, we fo und only one re se arch com pa ring the ef fects of US and LLLT on ex pe ri men tal wo und hea ling. 22 In that study, De mir et al used an in ci si onal wo und mo del in which the 4 th and 10 th days we re ta ken in con si de-ra ti on to in ves ti ga te the histo pat ho lo gi cal chan ges. An gi o ge ne sis was not eva lu a ted in the ir study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation